Social stigma in epilepsy, a population-based study in Malaysia / Kheng-Seang Lim - Kheng, Seang Lim (2013)

(untitled)
This study aims to determine the magnitude of social stigma in epilepsy as measured by the public attitudes toward epilepsy, in the general as well as in a specific population, in Malaysia. The preliminary study showed that there is a significant impact of epilepsy on the employment in Malaysia, an indirect indicator to a need to study social stigma among Malaysian population. However, the systematic review revealed a need to develop a cross-culturally applicable quantitative scale measuring the public attitudes toward epilepsy, leading to the study on development and validation of a PATE (Public Attitudes Toward Epilepsy) scale, which is developed based on a stigmatization model. Factoring into personal and general domains led to a new concept of classifying the public attitudes toward epilepsy into personal and general attitudes. In order to be applied among Malaysian population, translation of the PATE scale Malay and Chinese languages was performed. Psychometric testing of this translated version showed that the Malay and Chinese translated PATE scales were valid and reliable. The study on students showed that the scale is easily applied among a homogenous group and can be used in a web-based design. In addition, attitudes of students were only better than the general population in the general domain but not in the personal domain, indicating that a significant discrepancy between the personal and general attitudes toward epilepsy. The study on teachers showed significant better attitudes among teachers as compared to the general population with tertiary education, suggesting that attitudes toward epilepsy may be job specific. Population studies showed that there was no significant difference in attitudes toward epilepsy between the Chinese and Malay populations. However, on subcategory analysis, Chinese had better attitudes toward social contact with people with epilepsy, indicating that Chinese patients with epilepsy might have less social restriction as compared with the Malay. In addition, the studies also demonstrated that each ethnic group had a unique urban-rural pattern of attitudes toward iii epilepsy, enable us to understand the cultural differences from the sociological perspectives.